The Syntax of Absolute Verbal Forms in Early Welsh Poetry: A Survey. (1st January 2021) - Rodway, Simon
This paper undertakes a comprehensive survey of the syntax of absolute forms of verbs in the corpus of early Welsh poetry known ashengerdd. Comparisons are made with the syntax of absolute forms in Old Irish, in Old Welsh and Old Breton, in Middle Welsh court poetry of the twelfth century onwards, and with those found in Middle Welsh prose texts.